Developing Preservice Teachers' Instructional Design Skills Through Case-Based Instruction: Examining the Impact of Discussion Format. (September 2019) - Koehler, Adrie A.; Ertmer, Peggy A.; Newby, Timothy J.
For more than 100 years, case-based instruction (CBI) has been an effective instructional method for building problem-solving skills in learners. While class discussion is often included as part of the CBI learning process, the impact on learning is unclear. Furthermore, little research has focused on how specific facilitation strategies influence the development of learners' problem-solving skills. This study examined the impact of case discussion facilitation strategies on the development of preservice teachers' problem-solving skills. Specifically, two discussion formats were compared: instructor-facilitated (class discussions guided by instructor-crafted prompts and an active facilitator) and instructor-supported (discussions guided by instructor-crafted prompts only). Results indicated that while preservice teachers' problem-solving skills improved in both sections of the course, individuals in the instructor-facilitated section demonstrated significantly higher scores on course activities and designed instructional activities at higher cognitive levels compared with preservice teachers who participated in the instructor-supported discussions. Results underscore the importance of an active facilitator in CBI.